Analisis Faktor Faktor Yang Mempengaruhi Ketidakberminatan Masyarakat Menabung Di Bank Syariah Indonesia - Ernita Ernita; Gwi Awal Habibah; Tarmizi Tarmizi (Jurnal Penelitian Ilmu Ekonomi dan Keuangan Syariah, 2023)
This thesis is a study that examines the factors that influence the disinterest in saving. The purpose of this thesis is to be able to determine whether or not there is a significant influence from location, knowledge and product, reputation, promotion and religiosity simultaneously or partially on disinterest in saving and to find out the most dominant variable on disinterest in saving. This study used a quantitative method using primary data by giving questionnaires to the community in the Muara Bulian sub-district, with a total sample of 160 respondents. The analysis technique used is multiple regression analysis technique. carry out various tests such as the classic assumption test to check the health of the data, simultaneous (F) and partial (t) tests in order to find out the influence or not of the variables used, multiple liner tests, determinant coefficients and effective contributions in order to find out the dominant variable in influencing disinterest save until you can draw conclusions. The results of the conclusions of this study are as follows: (1) Simultaneously and partially indicate that location, knowledge and products, reputation, promotion and religiosity have a positive and significant effect on people's disinterest in saving in Islamic banks (2) The variable that has the greatest influence on disinterest in saving is a variable of knowledge and product that is equal to 18%